Psychological characteristics of intergenerational between generations among families (Actual Problems of Psychology in Educational Institutions, 2023)
The article comprehensively considers the problems ofinteraction between generations in the family. The author emphasizesthat it is especially important today to create conditions for theintergenerational transmission of culture, which would include the flowof information not only from the older generation to the younger, butalso back, since the youth’s interpretation of the current situation andcultural heritage undoubtedly affects the older generation. The concept ofsuccession of generations is defined, an analysis of psychological studies ofrelations between generations is given, personal factors, family relationsand education between and within generations are characterized.
Keywords: interaction, intergenerational interaction, younger generation, older generation, personal factors, family relations, upbringing